Characterization of Complete Land to Improve Rice Cultivation In Kendal District - Yulis Hindarwati; Meinarti Norma Setyapermas; Sri Minarsih; Agus Supriyo (Future Science, 2022)
Saline land in coastal areas has the potential for expansion of agricultural areas for food crops, especially rice when considering the availability of water and choosing the right planting time. Field experiments were carried out to know the characterization of saline land suitable for rice cultivation. The study was located in Purwokero Village, Brangsong District, Kendal Regency in 2018 ing soil samples before treatment and after ameliorant treatment, namely 25 days and 48 days from the research location. The study used a randomized block design with 2 treatment factors. Factor I is the inundation height (G) which consists of 0-10 cm inundated land (G1), 10-20 cm inundated land (G2). Factor 2 is the addition of ameliorant (A) consisting of: Humid Acid (A1), Zeolite (A2), and Gypsum (A3). Each treatment was repeated 4 times. Soil observation parameters were nutrient content consisting of acidity (pH), H2O, C organic, N total, P2O5 available, exchangeable cations (K, Na, Ca, Mg), and Electrical Conductivity (DHL) as well as heavy metal content consisting of: As, Hg, and Cd. Observational data were analyzed descriptively comparatively. The results showed that the special rice fields for the study included saline land due to seawater intrusion, which were characterized by DHL>4 ds, pH<8.8, SAR <13 and ESP<15 and identified heavy metal contaminants As, Hg, and Cd. The use of ameliorant materials in the form of humic acid and phytoremediation for heavy metal contaminants in improving saline soil quality.